1993
DOI: 10.1111/j.1442-200x.1993.tb03059.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of 19 infants with apparent life‐threatening events: Relationship between apnea and esophageal dysfunction

Abstract: There are various identifiable diseases or conditions that can cause apparent life‐threatening events (ALTE; e.g. gastroesophageal reflux (GER) and seizures). Nineteen infants with ALTE (mean age: 4.3 months) were brought to our hospital between June 1986 and August 1991. The causes of these ALTE were investigated. Analysis of laboratory data, radiological studies and esophageal function tests led to the diagnosis of GER in six of 19 infants; pertussis in five; upper respiratory infection in three; vagotonia‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The relationship of epileptiformic seizures and the presence of gastroesophageal reflux is discussed in the literature in regard to the diagnostic challenge distinguishing epileptic seizures from apneic events due to GER [17,18,[20][21][22]. Furthermore, both apparent life threatening events and apneic seizures are often found in association with GER [15,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of epileptiformic seizures and the presence of gastroesophageal reflux is discussed in the literature in regard to the diagnostic challenge distinguishing epileptic seizures from apneic events due to GER [17,18,[20][21][22]. Furthermore, both apparent life threatening events and apneic seizures are often found in association with GER [15,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Considering all the potential adverse outcomes, there is clearly a desire for prevention of future ALTE events. Finally, there is significant evidence implicating GERD as one causative factor of ALTE [2][3][4][5][6][7][8][9][10][11][12]. Gastroesophageal reflux disease is the most common diagnosis made in patients with ALTE, and the reported incidence varies between 26% and 53% [5,[7][8][9]11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, several investigators have attempted to determine the etiology of these events. Many believe that gastroesophageal reflux disease (GERD) may be a causative factor of ALTE because multiple reports have implicated GERD as an etiology [2][3][4][5][6][7][8][9][10][11][12]. Some authors have forwarded recommendations on the treatment of GERD-associated ALTE, most of which center upon medical management [13][14][15].…”
mentioning
confidence: 99%
“…[62] Over 80% of infants with ALTE appear to have no acute distress by the time they are seen at the emergency department [63] and no specific diagnosis can be found in up to 30% of those infants seen. [60] In a systematic review of 8 non randomised descriptive studies [56,57,[64][65][66][67][68] the most common diagnoses made in cases of ALTE were gastro-oesophageal reflux disease (GORD), which was reported in all studies and comprised 31% of total diagnoses, lower respiratory tract infection including pertussis and respiratory syncytial virus infection were reported in 5 studies and 8% of all diagnoses, and seizure was reported in 7 studies and 11% of all diagnoses. [55] Other diagnoses were problems with ear, nose and throat (3.6% of all diagnoses), cardiac problems (0.8%), urinary tract infection (1.1%), metabolic disease (1.5%), ingestion of drugs or toxins (1.5%), breath holding (2.3%), and factitious illness (0.3%).…”
Section: The Relationship Between Apparent Life Threatening Events (Amentioning
confidence: 99%